(untitled) (World Bulletin of Social Sciences, 2024)
Traditional medicine includes the cultural wisdom and knowledge of a society, including traditional healing methods passed down from generation to generation. Despite its rich history and effectiveness in treating various diseases, traditional medicine faces challenges and opportunities in modern healthcare. This article examines the challenges faced by traditional medicine, such as uncertainty, lack of standardization, and risks associated with unregulated practice. It also explores the promising future of traditional medicine, including innovation, integration with modern healthcare systems, community empowerment, and advances in research. By exploring barriers and potential pathways forward, we can better understand the complexities of traditional medicine and its role in modern healthcare